Educational Marketing as a Strategy for the Satisfaction of University Students - Gordillo, Liliana D.J. (2020)
In a globalized and competitive world, the need for the Higher Education Institutions to have a competitive advantage and exceed the expectations of the learners becomes more and more imperative, although the fundamental part of the Institutions is also true in addition to capturing enrollment is to retain it. and to retain it, and to achieve the above, it requires student satisfaction, so the objective of this research was to propose educational marketing as a strategy for student satisfaction at the Polytechnic University of Francisco I, Madero (UPFIN). The study has a quantitative approach of a descriptive type, it was applied to a sample of 361 UPFIN students and some results were that in order to achieve student satisfaction, variables such as: teaching videos, digital library service, linkage with microenterprises, extra classes for those who fail, overtime teaching second language, psychological and social guidance, study guide to present exams, classrooms and laboratories in good condition, plan according to the race, congresses and symposium in different careers, student involvement in research projects, friendly treatment of administrative staff, scholarships for student tickets, demonstrations and training with microentrepreneurs and the general public of what is done in the university.